Quantification of total phenol, in vitro investigation of antioxidant activity, cytotoxic effect and phytochemical screening of the leaf extract of artocarpus lacucha - Shoshe, Tamanna Zafrin (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017